Programming Effects of Prenatal Glucocorticoid Exposure with a Postnatal High-Fat Diet in Diabetes Mellitus - Sheen, Jiunn-Ming (Int J Mol Sci, 2016)
Increasing evidence has shown that many chronic diseases originate from early life, even before birth, through what are termed as fetal programming effects. Glucocorticoids are frequently used prenatally to accelerate the maturation of the lungs of premature infants. High-fat diets are associated with insulin resistance, but the effects of prenatal glucocorticoid exposure plus a postnatal high-fat diet in diabetes mellitus remain unclear. We administered pregnant Sprague-Dawley rats’ intraperitoneal dexamethasone (0.1 mg/kg body weight) or vehicle at gestational days 14–20. Male offspring were administered a normal or high-fat diet starting from weaning. We assessed the effects of prenatal steroid exposure plus postnatal high-fat diet on the liver, pancreas, muscle and fat at postnatal day 120. At 15 and 30 min, sugar levels were higher in the dexamethasone plus high-fat diet (DHF) group than the vehicle plus high-fat diet (VHF) group in the intraperitoneal glucose tolerance test (IPGTT). Serum insulin levels at 15, 30 and 60 min were significantly higher in the VHF group than in the vehicle and normal diet group. Liver insulin receptor and adenosine monophosphate-activated protein kinase mRNA expressions and protein levels were lower in the DHF group. Insulin receptor and insulin receptor substrate-1 mRNA expressions were lower in the epididymal adipose tissue in the VHF and DHF groups. “Programming” of liver or epididymal adipose tissue resulted from prenatal events. Prenatal steroid exposure worsened insulin resistance in animals fed a high-fat diet.